Bypassing Bariatric Costs and Cutting Rates of Surgical Site Infection - Baker, Celina (Operating Room Nurses Association of Canada Journal, 2018)
The Bariatric Program at The Ottawa Hospital Civic Campus (TOH-CC), which was designated as a Bariatric Centre of Excellence (BCOE) on February 10, 2017, has identified and implemented key changes in order to be more cost-efficient while providing patients with world-class care. The Bariatric Comprehensive Unit-Based Safety Program (CUSP) team modified its surgical technique and has been successful in not only reducing the cost per case but also in substantially decreasing the rates of surgical site infections (SSIs). The Bariatric CUSP team, evaluated current practices, identified an area for improvement, and successfully implemented an alternative surgical technique. The team has, as a result, reduced its SSI rate from 8% to 1%, in 2 years, and has saved over 250,000 (26 per cent) in costs per year during this period.